Breast Cancer Metastases Based on Molecular Subtypes at RSUD Dr. H. Abdul Moeloek Lampung - Nurmayeni; Islamy, Nurul; Tjiptaningrum, Agustyas; Siregar, Bintang Abadi; Kusumaningtyas, Aditya; Windarti, Indri (RSUP Dr. Kariadi, 2023)
BACKGROUND:Breast cancer is the most common cancer in Indonesia and is a leading cause of cancer-related deaths in the country. Metastases are responsible for most deaths among breast cancer patients. Breast cancer is typically classified into four subtypes based on immunohistochemistry: luminal A, luminal B, HER2+, and TNBC. OBJECTIVE:To determine the association between the metastatic pattern of breast cancer and their molecular subtypes at RSUD Dr. H. Abdul Moeloek Lampung. METHOD:This study was an observational analytic study with a cross-sectional design. The sample comprised 81 individuals who had suffered from breast cancer and were recorded in the medical records section of RSUD Dr. H. Abdul Moeloek Lampung between 2013 – 2021 and met the inclusion and exclusion criteria. The association between breast cancer subtypes and the incidence and metastase sites were tested using the Chi-Square test. RESULT:This study found a significant association between breast cancer subtypes and the incidence of metastases (p <0.05). The TNBC subtype had a more frequent rate of metastases (34.5%) than the other subtypes (31% luminal B, 20.7% luminal A, and HER2+ 13.8%). The study also revealed a relationship between ER status and the incidence of metastases (p < 0.05). The luminal A subtype tends to metastasize to the liver, luminal B tends to metastasize to the bone, HER2+ tends to metastasize to the lung and liver, and TNBC tends to metastasize to the lung. However, no significant association was found between breast cancer subtypes and metastatic sites. CONCLUSION:There was a significant association between breast cancer subtypes and the incidence of metastases, but not with the metastatic sites.